Study of biochemical changes in breast feeding women - Zahra Hammoudat (College of Education for Pure Sciences, 2006)
This research is concerned to measure some biochemical variables of fifty lactating women non pregnant comparing with fifty women neither lactating nor pregnant of the same age. of lactating once. The blood serum concentration of total protein, albumin, globulin, alkaline phosphates, calcium, phosphorus, sodium, potassium and hemoglobin were determined. The results showed decline concentration of total protein, globulin and calcium in addition to high concentration of phosphorus and sodium is found in the serum of women lactating, while the results showed no significant differences of values of albumin, alkaline phosphates, potassium and hemoglubin. Also, the result showed that the intake on not intake of milk by lactating mothers had no impact on the biochemical variables. Finally, the concentration of albumin decreased in the first month of lactation, while, in the letar lactation months there is increase concentration of alkaine phosphates and decline concentrations of sodium and potassium.